Effects of dietary N-carbamylglutamate on rumen fermentation parameters, and bacterial community diversity of Holstein dairy cows in Tibet - Zhu, Jinjia; Wu, Yicheng; Jiang, Aoyu; Li, Bin; Ran, Tao; Zhou, Chuanshe; Xiao, Dingfu; Tan, Zhiliang (Frontiers in Microbiology, 2023)
The Tibetan Plateau is characterized by low temperature and hypoxia. N-carbamylglutamic acid (NCG) can promote the endogenous synthesis of arginine (Arg) and increase blood oxygen saturation, and have the potential to be used to prevent the high-altitude hypoxia stress state of cows and improve their production performance. However, its beneficial effect on the rumen microbiota of Holstein dairy cows in the Tibet plateau remains unclear. Hence, the present study investigated the effects of the dietary NCG supplementation on fermentation parameters and rumen microflora of Holstein dairy cows in Tibet. Twelve multiparous (parity ranged from 2 to 7) Holstein dairy cows (413.0 ± 42kg) were randomly assigned to 2 treatments with 6 replicates in each treatment: basal diet (CON, control group) and basal diet plus 20 g/d/cow of NCG (NCG, experiment group), respectively. The experiment lasted for 45 days, with 15 days of pre-feeding and 30 days of formal trail period. The results showed that ruminal NH3-N concentration in NCG group was significantly lower (P < 0.05) than that in the CON group, while molar proportion of acetic acid and total volatile fatty acid concentration were significantly increased (P < 0.05) with the addition of NCG. Microbial diversity increased (P < 0.05) in NCG group, with Bacteroidetes, Firmicutes and Patescibacteria as the most abundant phylums. The KEGG pathway analysis showed that the potential function of ruminal bacteria were mainly enriched in metabolism (carbohydrates, amino acids, lipids, energy and nucleotides) and genetic information processing (replication, repair, translation). In conclusion, NCG can improve rumen nitrogen utilization, total VFA and acetic acid production, and increase rumen microbial diversity, all of which could make the introduced Holstein dairy cows to better adapt to the harsh environment in Tibet and improve their production performance.